Identifying Childhood Hunger in Maine - Mageean, Deirdre (Maine Policy Review, 1993)
Recent political campaigns at the national and state levels have been filled with much rhetoric about the present and future of families and children. But effective public policy developed in response to many pressing financial and social needs of families and children has not followed from the rhetoric. The lack of adequate quantitative research on the needs of children is often cited as a reason to move cautiously in responding to "perceived needs." Deirdre Mageean discusses the nation’s public policy responses to poverty that have been attempted since the mid-1960s. Mageean, who served as co-director of a year-long childhood hunger study, examines these poverty policies in the context of the findings of that study, the Maine Community Childhood Hunger Identification Project (CCHIP). The Maine CCHIP study, along with 20 others conducted under the auspices of the Food Research and Action Center (FRAC) in recent years, have begun to fill some of the data needs of state and federal policymakers as they struggle to craft responsive and responsible poverty policies.